Makna Konten Influencer Parenting bagi Generasi Muda dalam Membangun Pola Asuh Masa Depan - Amelia Putri Pertiwi; Emilya Yohana Natasya; Nandito Nandito; Faisal Dudayef (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
The development of social media has made influencer parenting content one of the important sources of reference for the younger generation in understanding parenting. This study aims to examine the meaning of influencer parenting content for the younger generation in building future parenting. The research uses a qualitative approach with a literature review method on various scientific publications relevant to the topics of influencers, parenting, and digital media. The results of the study show that the younger generation interprets influencer parenting content not only as a source of practical information, but also as a reference for values and an ideal representation of the role of parents. The process of interpretation takes place actively and reflectively, influenced by personal experiences, family backgrounds, digital literacy levels, and socio-cultural contexts. In addition, the credibility of influencers and the style of delivering content also affect the acceptance rate of the audience. Influencer parenting content shapes a parenting discourse that emphasizes emotional awareness, empathic communication, positive parenting, and concern for children's mental health. Thus, the future parenting of the young generation is understood as a dynamic, adaptive, and constantly evolving social construction, with digital media as one of the main shaping factors.